PENGARUH KONSENTRASI GARAM YANG BERBEDA PADA PEMBUATAN TELUR ASIN AYAM RAS TERHADAP KARAKTERISTIK RASA DAN TINGKAT KEMASIRAN KUNING TELUR - Kurniawati; Doso Sarwanto; Tri Sukmaningsih; Sari Tuswati (MEDIA PETERNAKAN, 2023)
The study was aimed to determine the effect of  different salt concentrations on the taste characteristics of salted eggs yolk and the level of grittiness texture. This research was conducted on 1th July until 30th November 2022 at Animal Production Technology Laboratory of Animal Husbandary Wijayakusuma University, Purwokerto. The materials used were 40 eggs, brick powder, salt and water. This research was carried out with an experimental method. The experimental design used a completely randomized design (CRD) with 5 treatments, each treatment consisting of 2 eggs and repeated 4 times. The variables measured in this study were the taste characteristics of the salted egg and the level of grittiness texture. The research that the different salt concentrations had a significant influence on the taste characteristics of salted eggs and the level of grittiness texture (p<0.05). Furthermore, based on the BNT test, it was found that the taste characteristics and grittiness of P1 were significantly different from P2, P3, P4 and P5. P5 was the saltiest taste and the richest texture of grittiness, while P1 was the treatment with the least salty taste and the least grittiness texture. Key answer : Salted egg, salt concentration, taste characteristics, the level of grittiness texture